Los juzgados administrativos. ¿Son la solución a la congestión de la jurisdicción? (2006)
Colombian administrative law courts, traditionally have shown huge processes congestion. In orden to solve this difficulty, law created 257 new administrative courts, that, all at once, from their very begining, are extremely crowded too. The author proposes three ways to solve the problem: 1) To accept only the legal proceding having legal viability; 2) To restrict, inside real necessity, to decree and to practice evidences; 3) using thelephonic communications, to managed, that litigigants and assistants of justice, collaborate.